The future of a promise and the promise of a future: China and India. Issue 1 (2nd January 2020) - Abraham, Itty
ABSTRACT: This response to Ashish Rajadhyaksha's essay reflects on the following themes: state promises made and broken, comparing India and China, and science fiction as national redemption.